INTERAKSI ANTARA Hoya diversifolia Blume (ASCLEPIADACEAE) DENGAN SEMUT (FORMICIDAE) DI KEBUN RAYA BOGOR - Rahayu, Sri; Qoyim, Ibnul; Budhiastuti, Ninik (Buletin Kebun Raya, 2007)
Interaction between epiphyte Hoyo diversifolia Blume (Asclepiadaceae) and ants (Formicidae) was observed in Bogor Botanical Garden. Five species of ants were noted to be involved in the interaction, namely Acropygo sp., Pseudolosius sp., Oecophylla sp., Myrmoteros sp. and Euprenotepis sp. They exhibit a mutualism symbiotic interaction in an optional (facultative) manner. The ants take some advantages of floral and extra floral nectarines for food and apparently receive protection for their nests by seedlings of H. diversifolia. Meanwhile seed of H. diversifolia is carried out and dispersed by ants to some favourable sites to grow.